2022
DOI: 10.1371/journal.pone.0265726
|View full text |Cite
|
Sign up to set email alerts
|

Development of a national quality framework for palliative care in a mixed generalist and specialist care model: A whole-sector approach and a modified Delphi technique

Abstract: In a predominantly biomedical healthcare model focused on cure, providing optimal, person-centred palliative care is challenging. The general public, patients, and healthcare professionals are often unaware of palliative care’s benefits. Poor interdisciplinary teamwork and limited communication combined with a lack of early identification of patients with palliative care needs contribute to sub-optimal palliative care provision. We aimed to develop a national quality framework to improve availability and acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Recently in the Netherlands, there has already been an increased focus on relatives of patients receiving palliative care in the Netherlands, due to the published Netherlands Quality Framework of Palliative Care 36 . This study showed that monitoring of relatives during the palliative trajectory is necessary.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Recently in the Netherlands, there has already been an increased focus on relatives of patients receiving palliative care in the Netherlands, due to the published Netherlands Quality Framework of Palliative Care 36 . This study showed that monitoring of relatives during the palliative trajectory is necessary.…”
Section: Discussionmentioning
confidence: 82%
“…Care. 36 This study showed that monitoring of relatives during the palliative trajectory is necessary. It is important for healthcare professionals to support relatives throughout the patient's illness trajectory, especially those who are more vulnerable to a lower quality of life after the patient's death, that is, women, relatives with a lower EF prebereavement and relatives with lower social support during bereavement.…”
Section: Discussionmentioning
confidence: 89%
“…Respondents who did not describe themselves as generalist, specialist, or expert based on education or based on work-experience were categorized as generalists because of their initial education as HCPs. Thereby, we followed Boddaert et al [ 27 , 30 ] who described in the National Quality Framework Palliative Care: In the Netherlands, all HCPs are expected to provide generalist palliative care, informed by national standards and guidelines. Palliative care specialists can be consulted to provide support and expert advice [ 14 , 22 , 29 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Descriptive statistics were used to summarize baseline characteristics of healthcare professionals and to describe the number and percentages of self-described roles of HCPs, based on work experience and education. Hereby, we used the threefold distinction of generalist—specialist—expert, based on the context in the Netherlands and described in the Netherlands Quality Framework for Palliative Care (NQFPC) [ 27 , 30 ]. A Chi-square test was used to test for significant differences between self-description based on education or work experience and other characteristics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation